2021
DOI: 10.1080/00131911.2021.1955830
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional assessment of changes in higher education teaching and learning in the face of COVID-19

Abstract: COVID-19 has had a profound influence on the conduct of teaching and learning in higher education. Almost everywhere a sudden shift occurred as educators transitioned courses from mainly face-to-face teaching and learning to emergency remote instruction, mostly conducted online. While details varied for individual faculty members, institutions, and countries, all confronted new challenges. We examine the immediate effects of COVID-19 on teaching and learning in higher education. Our results are based on a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 15 publications
3
42
0
Order By: Relevance
“…Group assignments became less frequent, while exams contained more multiple-choice questions and fewer essay questions. These findings align with other recent studies on the effects of the pandemic on assessment practices (Almossa & Alzaharani, 2022;Bartolic et al, 2021;Senel & Senel, 2021). Because exams were required for accountability purposes, educational institutions (universities especially) conducted and invigilated them online using a variety of modalities (e.g., via platforms such as Zoom or proctoring).…”
Section: Changes In Assessment Practicessupporting
confidence: 87%
See 1 more Smart Citation
“…Group assignments became less frequent, while exams contained more multiple-choice questions and fewer essay questions. These findings align with other recent studies on the effects of the pandemic on assessment practices (Almossa & Alzaharani, 2022;Bartolic et al, 2021;Senel & Senel, 2021). Because exams were required for accountability purposes, educational institutions (universities especially) conducted and invigilated them online using a variety of modalities (e.g., via platforms such as Zoom or proctoring).…”
Section: Changes In Assessment Practicessupporting
confidence: 87%
“…The results from RQ2 showed that teachers became more flexible in their evaluation strategies, lowering their assessment criteria and standards and amending grading procedures. Again, these findings accorded with other similar studies (Bartolic et al, 2021;Montenegro-Rueda et al, 2021). Reasons for these adjustments included reduced instructional contact; setting up online classes was difficult, and the participants suggested that they wanted to alleviate screen time for students and help them cope with complex living situations such as domiciliary lockdowns.…”
Section: Changes In Assessment Practicessupporting
confidence: 77%
“…Most questionnaires and interviews were completed from May to August of 2020. Fuller details of the study are available in Bartolic et al (2021) and Guppy et al (2021). The data collection instruments are available at https://blogs.ubc.ca/covid 19tra nsiti on/.…”
Section: Methodsmentioning
confidence: 99%
“…What we found was some variation in teachers' proficiency between institutions. More broadly, there was consistent evidence that the effects of the public health edicts were so sudden, and so disruptive, that digital experience and proficiency had little impact on the success instructors felt in rapidly refashioning their courses (Bartolic et al 2021). This represents a substantial difference between using technologies as a complement to most pre-COVID-19 course delivery and using technologies as the unique vector of teaching and learning, as was necessary post-pivot.…”
Section: Discussionmentioning
confidence: 99%